2019
DOI: 10.1093/pcp/pcz080
|View full text |Cite
|
Sign up to set email alerts
|

Comparative RNA-Sequencing and DNA Methylation Analyses of Apple (Malus domestica Borkh.) Buds with Diverse Flowering Capabilities Reveal Novel Insights into the Regulatory Mechanisms of Flower Bud Formation

Abstract: In plants, DNA methylation (i.e. chromatin modification) is important for various biological processes, including growth, development and flowering. Because ‘Fuji’ apple trees are alternate bearing and have a long ripening period and poor-quality flower buds, we used bud types with diverse flowering capabilities to investigate the epigenetic regulatory mechanisms influencing flower bud formation. We examined the DNA methylation changes and the transcriptional responses in the selected apple bud types. We obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 70 publications
4
27
0
Order By: Relevance
“…Previous studies have shown that DNA was methylated differently at different genetic regions, which also could affect gene expression (Ibarra et al, 2012;Liu et al, 2015). More methylated DNAs were found upstream of a gene in certain plants (Xing et al, 2019(Xing et al, , 2020. However, in the present study, the CG methylation of gene-body was significantly higher than that in other regions, which was consistent with earlier reports in strawberry, orange, and peach (Cheng et al, 2018;Huang et al, 2019;Zhu et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Previous studies have shown that DNA was methylated differently at different genetic regions, which also could affect gene expression (Ibarra et al, 2012;Liu et al, 2015). More methylated DNAs were found upstream of a gene in certain plants (Xing et al, 2019(Xing et al, , 2020. However, in the present study, the CG methylation of gene-body was significantly higher than that in other regions, which was consistent with earlier reports in strawberry, orange, and peach (Cheng et al, 2018;Huang et al, 2019;Zhu et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…However, mCHH accounted for the highest proportion of total mC in the study, followed by the CG and CHG context. These findings are consistent with studies in apple trees, M. hupehensis, and cotton (Xu et al, 2018;Xing et al, 2019Xing et al, , 2020Zhang et al, 2020). It is worth noting that CHH methylation remained elevated during grain filling (38-46%) and CG and CHG methylation showed the opposite trend (33-29 and 29-25%, respectively).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…2020 ), flower bud formation in apple ( Malus domestica Borkh.) ( Xing et al. 2019 ) and physiological responses in Arabidopsis ( Arabidopsis thaliana ) roots under zinc deficiency ( Chen et al.…”
Section: Assessing Plant–environment Interactions Over Timementioning
confidence: 99%